Daniel N. Cárdenas, "Acoustic vowel loops of two Spanish idiolects", en Phonetica, Münster, 5 (1960), pp. 9-34. - Navarro Tomás, Tomás (El Colegio de México, 1960)
Se reseñó: "Acoustic vowel loops of two Spanish idiolects".